Continuous professional development for physicians - Ghosh, Amit (MedUNAB, 2013)
Maintenance of professional competence remains an exercise of permament learning and an essential requirement for evidence –based medical practice. Physicians attend continuing professional development (CPD) programs to acquire new knowledge. Often CPD programs remain the main source for updates of information. CPD organizers have a considerable responsibility in determining appropriate curriculum for their conferences. Organizing an effective CPD activity often requires understanding of the principles of adult education. Prior to deciding on the curriculum for a CPD, course organizers should conduct needs assessment of physicians. CPD planners should create activities that would consistently improve physician competence. CPD sessions that are interactive, using multiple methods of instructions for small groups of physicians from a single specialty are more likely to change physician knowledge and behavior. The effectiveness of a CPD program should be evaluated at a level beyond measuring physician satisfaction. CPD planners should incorporate methods to determine the course attendees’ improvement of knowledge, skills and attitudes during the CPD activities. Pre and post conference evaluations of physicians using multiple choice questions may form a useful method of assessment.